(untitled) (Altre Modernità, 2017)
This paper examines the relationship between language teachers and the errors made by their students. Traditionally, errors reflect a deviation from a standard, which is a described or imagined standard form of linguistic behavior, and teachers are the repositories of that standard. Errors also provide insights into processes of language acquisition, and offer teachers convenient strategies for classroom intervention. The appearance of contrastive analysis in the 1960s, the brief ascendancy of error analysis, and the ensuing development of inter-language studies, kept the focus firmly on the learner’s distance from native speaker competences, and the teacher’s role to bring students as far as possible towards a native-speaker like use. With the appearance of the Common European Framework of Reference the focus shifted from learner error to learner competence. Nonetheless, a standard form of the language continued to provide the target in coursebooks, and an ostensibly communicative approach continued to be the vehicle for a grammatical syllabus. But recently further challenges have been posed by the growth of English Lingua Franca (ELF) and the awareness that most interactions in English are now between non native speakers (NNSs). ELF research shows that success in NNS interaction does not come from approximating native speaker norms, but rather from a range of collaborative strategies. In this context, teachers and testers will increasingly have to redefine the notion of “error” in the language classroom, an operation which is likely to entail a painful paradigm shift.